2017
DOI: 10.1111/1750-3841.14013
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Grinding at Modified Atmosphere or Vacuum on Browning, Antioxidant Capacities, and Oxidative Enzyme Activities of Apple

Abstract: This study evaluated the effects of grinding at atmospheric pressure (control), under vacuum (ß2.67 kPa), or with modified atmosphere (N 2 and CO 2 ) on the browning, antioxidant activity, phenolics, and oxidative enzyme activity of apples as a function of time. The control group was affected most, showing distinct browning and losing most of the antioxidant activity and concentrations of the main phenolic compounds. The modified atmosphere groups retained color, antioxidant activity, and phenolic compounds be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…31 In freeze-dried samples, these reactions do not occur because the freezing and subsequent sublimation of water under vacuum conditions prevents the action of these enzymes and consequently the browning of the samples. 32 However, although this process efficiently preserves bioactives, freeze-drying costs can be 2-5 times higher than hot air-drying in order to achieve the same final moisture content. This fact justifies the need to find alternatives for the production of economically affordable healthy food for everyone.…”
Section: Effect Of Apple Processing On the Phenol Stabilitymentioning
confidence: 99%
“…31 In freeze-dried samples, these reactions do not occur because the freezing and subsequent sublimation of water under vacuum conditions prevents the action of these enzymes and consequently the browning of the samples. 32 However, although this process efficiently preserves bioactives, freeze-drying costs can be 2-5 times higher than hot air-drying in order to achieve the same final moisture content. This fact justifies the need to find alternatives for the production of economically affordable healthy food for everyone.…”
Section: Effect Of Apple Processing On the Phenol Stabilitymentioning
confidence: 99%
“…Liu et al [44] had proved POD catalyzed various oxidation reactions involving CAT and caused enzymatic browning with PPO. Kim et al [45] also showed that PPO and POD were crucial for the oxidation of phenolic compounds and resulted in enzymatic browning. Liu et al [44] also found that POD was related to anti-browning of fresh-cut potato slices during storage.…”
Section: Related Enzyme Activitiesmentioning
confidence: 99%
“…More than 50 per cent of foods susceptible to browning are wasted due to discolorations caused by enzymatic reactions [5]. Undesirable endogenous enzymatic reactions occur during intermediate processing operations such as fruit washing, cleaning, sorting, peeling, coring and cutting [6]. Polyphenol oxidase (PPO) and peroxidase (POD) are the two enzymes responsible for the oxidative browning reactions.…”
Section: Introductionmentioning
confidence: 99%